Profil Pemecahan Masalah Higher Order Thinking Skill Ditinjau dari Self-Eficacy Siswa - Putri Wulandari; Nurcholif Diah Sri Lestari; Inge Wiliandani Setya Putri; Dian Kurniati; Saddam Hussen (Jurnal Tadris Matematika, 2023)
The phenomenon of students not being used to solving higher order thinking questions often occurred in one of the Islamic Senior High School in Sidoarjo. Therefore, this research aims to describe the profile of students' problem-solving in overcoming HOTS questions based on the self-efficacy. The research subjects were three selected students of XI-IPA class who were categorized into low, moderate, or high self-efficacy based on self-efficacy questionnaires and had good communication skills. The data were collected through tests, triangulated by interviews and analyzed using Polya's problem-solving indicators (unerstanding the problem, devising a plan, carrying the plan, and looking back). The results show that: 1) Students with low self-efficacy able to solve an “analyze” problem eventhough without looking back and solve the “evaluate” problem through all of the stages. Eventhough, he need help to work on the “creative” problem; 2) Students with moderate self-efficacy able to solve an “analyze” problem through all stages. However, while working on evaluate and creative problem, he could only complete the stages of understanding the problem, devise an incomplete plan and never try to carry out the plan; 3) Students with high self-efficacy can solve the problem on analyze, evaluate, and create in a complete stage. Teachers must become accustomed to asking HOTS questions to students in order to increase student self-efficacy and problem-solving abilities.